Cartilage Intermediate Layer Protein 2 (CILP-2) Is Expressed in Articular and Meniscal Cartilage and Down-regulated in Experimental Osteoarthritis - Bernardo, Bianca C. (American Society for Biochemistry and Molecular Biology, 2011)
Using transcriptome profiling to determine differential gene expression between the permanent mouse articular cartilage and the transient growth plate cartilage, we identified a highly expressed gene, Cilp2, which is expressed differentially by articular chondrocytes. CILP-2 is highly homologous to CILP-1 (cartilage intermediate layer protein 1), which is expressed in the intermediate zone of articular cartilage and has been linked to cartilage degenerative diseases. We demonstrated that Cilp2 has a restricted mRNA distribution at the surface of the mouse articular cartilage during development, becoming localized to the intermediate zone of articular cartilage and meniscal cartilage with maturity. Although the extracellular CILP-2 protein localization is broadly similar to CILP-1, CILP-2 appears to be more localized in the deeper intermediate zone of the articular cartilage extracellular matrix at maturity. CILP-2 was shown to be proteolytically processed, N-glycosylated, and present in human articular cartilage. In surgically induced osteoarthritis in mice, Cilp1 and Cilp2 gene expression was dysregulated. However, whereas Cilp1 expression was increased, Cilp2 gene expression was down-regulated demonstrating a differential response to mechanically induced joint destabilization. CILP-2 protein was reduced in the mouse osteoarthritic cartilage. Ultrastructural analysis also suggested that CILP-2 may be associated with collagen VI microfibrils and thus may mediate interactions between matrix components in the territorial and inter-territorial articular cartilage matrix. mRNA expression analysis indicated that whereas Cilp1 and Cilp2 are expressed most abundantly in cartilaginous tissues, expression can be detected in muscle and heart.